Etlingera Elatior Inflorescence Extract Mitigates Acute Gastric Ulcers by Suppressing the Expression of Inducible Nitric Oxide Synthase in Ethanol-Induced Wistar Rats - Prayoga DK; Aulifa DL; Budiman A; Levita J; Jiranusornkul S (Journal of Experimental Pharmacology)
Deshanda Kurniawan Prayoga,1,* Diah Lia Aulifa,2,* Arif Budiman,3,* Jutti Levita,4,* Supat Jiranusornkul5,* 1Doctoral Program in Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, Indonesia; 2Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Padjadjaran University, Sumedang, Indonesia; 3Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Padjadjaran University, Sumedang, Indonesia; 4Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, Indonesia; 5Department of Pharmaceutical Science, Faculty of Pharmacy, Chiang Mai University, Chiang Mai, Thailand*These authors contributed equally to this workCorrespondence: Jutti Levita, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 46363, Indonesia, Email jutti.levita@unpad.ac.idBackground: Ethanol consumption by oral route can induce gastric cell necrosis and vascular damage due to excessive reactive oxygen species (ROS) production. ROS activates the translocation of NF-κB to the nucleus and increases iNOS expression, an enzyme that catalyzes nitric oxide (NO) production, eventually disrupting gastric protective mechanisms and contributing to ulcer formation. Etlingera elatior inflorescence, which has been traditionally used to alleviate stomach discomfort, was reported to possess anti-inflammatory activity. However, such a study on the downregulation of the iNOS expression is lacking.Purpose: To confirm the gastro-protective and anti-ulcer effects of the E. elatior inflorescence (EEIE) extract via downregulation of iNOS expression in ethanol-induced gastric ulcer rats.Methods: The fresh inflorescence petals were collected from West Java, Indonesia, and were extracted using 70% ethanol. The effects of 5 days of oral administration of EEIE were studied in ethanol-induced adult male Wistar rats by examining the weight gain percentage, feed residue, stomach ratio index, and microscopic and macroscopic evaluation of gastric mucosal damage. Subsequently, the iNOS expression in the rats’ stomach was Western blotted by employing β-actin as the loading control.Results: EEIE reduced weight gain percentage but did not show a significant difference in feed residue. EEIE increased the stomach ratio index, and at a dose of 625 mg/kg BW, significantly reduced the ulcer index, providing 100% protection (p < 0.05) to rats while decreasing inflammatory cell infiltration. EEIE inhibited the expression of iNOS in both cleaved and full-length forms at this dose.Conclusion: Etlingera elatior inflorescence may have the potential to mitigate acute gastric ulcers by downregulating the expression of iNOS in ethanol-induced Wistar rats. However, further studies are needed to confirm its role in alleviating chronic ulcer models.Keywords: acute inflammation, etlingera, gastric ulcers, iNOS, medicinal plants, zingiberaceae